2001
DOI: 10.1038/sj.jim.7000021
|View full text |Cite
|
Sign up to set email alerts
|

The influence of plasticiser on molecular organisation in dry amylopectin measured by differential scanning calorimetry and solid state nuclear magnetic resonance spectroscopy

Abstract: The interaction of crystalline and amorphous amylopectin with the plasticisers glycerol and ethylene glycol in the absence of water was studied with differential scanning calorimetry (DSC) and solid state NMR. At room temperature glycerol interacts mainly with the amorphous regions, while for ethylene glycol the amylopectin crystallinity does not effect the interaction. After heating the mixtures, an additional immobilisation of the plasticiser occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…This confinement effect is accompanied by a general delay in the dynamics of dispersed EG, due to interaction of EG molecules with partially dissolved AP chains in the EG rich phase. These results are in agreement with previously reported data on the interaction between starch polysaccharides and glycerol or ethylene glycol, which showed that time as well as heat strongly immobilize the plasticizer. , …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This confinement effect is accompanied by a general delay in the dynamics of dispersed EG, due to interaction of EG molecules with partially dissolved AP chains in the EG rich phase. These results are in agreement with previously reported data on the interaction between starch polysaccharides and glycerol or ethylene glycol, which showed that time as well as heat strongly immobilize the plasticizer. , …”
Section: Discussionsupporting
confidence: 94%
“…Insight into the plasticizer−macromolecule interaction is essential for the optimization of the material properties of thermoplastic starch by controlling the molecular structure. Recently, the interactions of glycerol and ethylene glycol with dry starch polysaccharides (amylose and amylopectin) were investigated using DSC and solid-state NMR spectroscopy, showing that for both plasticizers a strong interaction is induced by heat and time. , The interaction of starch with ethylene glycol develops more rapidly than with glycerol.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that amylopectin and starch undergo an oxidation reaction with Na silicate, resulting in the formation of, most likely, a carboxyl group (CO–O) which is normally characterized by an NMR chemical shift at around 168 ppm 43. The formation of the carboxyl group probably takes place at the C6 terminal since the C6 carbon is more mobile than the other carbon atoms and has two directly bound protons, in contrast to the other carbons that only have one proton 44, 45. The presence of a carbonyl linkage via interaction with the C2 and C3 carbon atoms of the pyranose ring was proposed by Zhou et al 46.…”
Section: Resultsmentioning
confidence: 95%
“…This category of reported studies show a theoretical basis for the observation of aging presented in different TPSs and the change in MW using various methods such as the dynamic mechanical thermal analysis (DMTA) 134, XRD 135, DSC 136–139, AFM 140–142, SEM, high‐resolution optical microscopy 143–145, gel permeation chromatography 146–150, NMR spectroscopy 76, 133, 151, 152, and Fourier‐transform infrared spectroscopy 153, 154. The mobility of water in these systems was monitored using thermo‐plasticization studies of sorption and diffusion during storage 52, 113, 155.…”
Section: Biodegradation Retrogradation and Agingmentioning
confidence: 99%